Efficient Visible‐Light‐Excitable Eu3+ Complexes for Red Organic Light‐Emitting Diodes. Issue 14 (27th February 2020) - Francis, Biju; Nolasco, Mariela M.; Brandão, Paula; Ferreira, Rute A. S.; Carvalho, Rafael S.; Cremona, Marco; Carlos, Luís D.
Abstract : Visible‐light‐excited Eu 3+ complexes have received much attention in the last years due to the rapidly increasing demand for less‐harmful biomarkers and low‐voltage driven emitters in optoelectronics. Nevertheless, these complexes usually exhibit poor emission quantum yields, contrarily to the ones excited in the ultraviolet spectral region. To address this challenge, a series of complexes based on trivalent lanthanide ions, [Eu(bpyO2 )(CH3 OH)2 (H2 O)(NO3 )2 ](NO3 ) (1 ), [Gd(bpyO2 )(H2 O)4 (Cl)2 ]Cl (4 ), Ln(tta )3 (H2 O)(C2 H5 OH) Ln = Eu (2 ), Gd (5 ) and Ln(tta )3 (bpyO2 ) Ln = Eu (3 ), Gd (6 ), were synthesized using 2‐thenoyltrifluoroacetone (Htta ) as primary ligand and 2, 2'‐dipyridyl N, N' ‐dioxide (bpyO2 ) as neutral donor, and characterized, with special emphasis on their crystal structures and luminescence properties. Single crystal X‐ray diffraction revealed that the central metal ion has a coordination number of 9 in 1, and 8 in all other complexes. Complex 3 exhibited a broad excitation spectrum ranging from 250 to 480 nm, exhibiting, when compared to 1 and 2, higher absolute emission quantum yields of 0.46, 0.36 and 0.33, for excitation at 400, 425, and 450 nm, respectively. The theoretical intensity parameters, radiative and non‐radiative decay rates, and intrinsic and absolute emission quantum yields were assessed using the LUMPAC software displaying a very good accord with the experimental values. Moreover, organic light‐emitting diodes with a maximum efficiency of 5.7 × 10 –2 cd A –1 at 14 V were fabricated using 3 as an emitting layer. Abstract : A novel visible‐light‐excitable Eu 3+ complex has been synthesized. Its structural and optical characterizations are presented. The theoretical luminescence parameters assessed with LUMPAC software are in good accord with experimental values. Organic light‐emitting diodes with a maximum efficiency of 5.7 × 10 –2 cd A –1 at 14 V were fabricated using the developed complex as an emitting layer.